Report of the First International Consensus on Standardized Nomenclature of Antinuclear Antibody HEp-2 Cell Patterns 2014–2015 - Chan, Edward K. L.; Damoiseaux, Jan; Carballo, Orlando Gabriel; Conrad, Karsten; de Melo Cruvinel, Wilson; Francescantonio, Paulo Luiz Carvalho; Fritzler, Marvin J.; Garcia-De La Torre, Ignacio; Herold, Manfred; Mimori, Tsuneyo; Satoh, Minoru; von Mühlen, Carlos A.; et al. (Frontiers in Immunology, 2015)
During the 12th International Workshop on Autoantibodies and Autoimmunity (IWAA) held in Sao Paulo, Brazil, on August 28, 2014, a full day session was devoted to establishing a consensus on the nomenclature of staining patterns observed in the antinuclear antibody (ANA) indirect immunofluorescence test on HEp-2 cells. The current report summarizes the collective agreements with input from the host Brazilian and international communities that represented research, clinical, and diagnostic service laboratories. Patterns are categorized in three major groups (nuclear, cytoplasmic, and mitotic patterns) and each pattern has been defined and described in detail. The consensus nomenclature and representative patterns are made available online at the International Consensus on Antinuclear antibody Pattern (ICAP) website (www.ANApatterns.org). To facilitate continuous improvement and input, specific comments on ICAP are encouraged and these will be discussed in subsequent ICAP meetings. The ultimate goal with the establishment of the ICAP is to promote harmonization and understanding of autoantibody test nomenclature, as well as interpretation guidelines for ANA testing, thereby optimizing usage in patient care.